2018
DOI: 10.1186/s13068-018-1063-6
|View full text |Cite
|
Sign up to set email alerts
|

A fast and sensitive activity assay for lytic polysaccharide monooxygenase

Abstract: BackgroundLytic polysaccharide monooxygenases (LPMO) release a spectrum of cleavage products from their polymeric substrates cellulose, hemicellulose, or chitin. The correct identification and quantitation of these released products is the basis of MS/HPLC-based detection methods for LPMO activity. The duration, effort, and intricate analysis allow only specialized laboratories to measure LPMO activity in day-to-day work. A spectrophotometric assay will simplify the screening for LPMO in culture supernatants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
160
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(173 citation statements)
references
References 37 publications
8
160
3
2
Order By: Relevance
“…LPMO activity assay using 2,6‐dimethoxyphenol (2,6‐DMP) was performed as described by Breslmayr et al. (2018) . The standard reaction mixture for the LPMO activity assay contained 100 μ m H 2 O 2 , 1.0 m m 2,6‐DMP and 4 μ m of TaLPMO9A.…”
Section: Methodsmentioning
confidence: 99%
“…LPMO activity assay using 2,6‐dimethoxyphenol (2,6‐DMP) was performed as described by Breslmayr et al. (2018) . The standard reaction mixture for the LPMO activity assay contained 100 μ m H 2 O 2 , 1.0 m m 2,6‐DMP and 4 μ m of TaLPMO9A.…”
Section: Methodsmentioning
confidence: 99%
“…All these substrates show a common feature, namely the β-1,4 linkages connecting the single sugar moieties in the backbone. A fast and sensitive spectrophotometric (using 2,6-dimethoxyphenol as chromogenic substrate and H 2 O 2 as cosubstrate) assay for LPMO activity determination was developed to follow the production and purification as well as to study enzyme-binding constants or thermal stability [85]. α-1,4 bonds).…”
Section: Substrate Preferencesmentioning
confidence: 99%
“…Enzyme kinetics using 2,6-DMP as substrate (Breslmayr et al 2018) confirmed the oxidative activity of the enzyme. So the biochemical and structural information and the efficiency in lignocellulosic biomass conversion suggested that AfLPMO16 could be an important member of the Cellulase cocktail of industrial use.…”
Section: Introductionmentioning
confidence: 66%
“…2,6 DMP (2,6-dimethoxyphenol) was used as a substrate for AfLPMO16 in this study (Breslmayr et al 2018). The reaction was done in phosphate buffer (100mM pH 6.0) containing 10mM DMP, 5μM hydrogen peroxide, and 50μg of purified AfLPMO16 at 30 .…”
Section: Biochemical Assays Of Aflpmo16mentioning
confidence: 99%
See 1 more Smart Citation